Reviewing Business-IT alignment instruments under SAM dimensions - Belfo, Fernando Paulo (2013)
Business-IT alignment has been on the top of the concerns of IT executives for many years and how to assess it has been under research. Among many proposals, one of the best known and cited in the literature, showing some relevant empirical work, is the Luftman’s Strategic Alignment Maturity (SAM) categories assessment. Taking it as a framework, seven other proposals are examined using SAM categories as dimensions of business-IT alignment: communications, competency/value measurements, governance, partnership, technology scope and skills. Except for one proposal revealing a tactical level approach, this review shows that business-IT alignment assessment has been studied essentially at the strategic level. Among the examined dimensions across the several proposals, governance is the best covered one while the human resource skills dimension is considerably neglected. Having still room for improvements, either in the governance or the technology scope dimensions, the SAM assessment seems a well balanced instrument. The empirical work already found on SAM provides a good starting point to get an acceptable validated instrument. However, if in terms of content validity, SAM is one of the most promising instruments, there is still much work to do on what concerns its operationalization. Future research should strive for a rigorous, strong instrument on every component of construct validity, namely, the convergent, discriminant and nomological components.